Morphology of collagen fibers and elastic system fibers in actinic cheilitis - Sgarbi Flavia; Bertini Fernanda; Tera Tábata de; Cavalcante Ana Sueli (Wolters Kluwer Medknow Publications, 2010)
Background: Actinic cheilitis (AC) is a premalignant condition intimately related to exposure of the lips to sun rays. Aim: The objective of this study was to evaluate the elastic and collagen fibers in the lamina propria of AC. The degree of epithelial atypia was correlated with the quantity of elastic and collagen fibers. Materials and Methods: Fifty-one cases were investigated. One slide was stained with hematoxylin-eosin for the evaluation of atypia, the second was stained with Weigert′s resorcin-fuchsin for the assessment of elastic fibers, and the third slide was stained with Mallory′s trichrome for the analysis of collagen fibers. Results: Ordinal logistic regression analysis revealed a significant correlation between the presence of atypia and collagen fibers (P<0.05). Conclusions: It was concluded that there seems to be a reduction in the quantity of collagen fibers in cases of moderate and severe atypia. No correlation was observed between the degradation of elastic system fibers and the grade of dysplasia.